2020
DOI: 10.1155/2020/2963540
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Protects Dopamine Neurons via Inhibition of NLRP3 Inflammasome Activation in Microglia

Abstract: Neuroinflammation plays a crucial role in the pathological process of Parkinson’s disease (PD). Nod-like receptor protein 3 (NLRP3) inflammasome was highly located in microglia and involved in the process of neuroinflammation. Activation of the NLRP3 inflammasome has been confirmed to contribute to the progression of PD. Thus, inhibition of NLRP3 inflammasome activation could be an important breakthrough point on PD therapy. Ellagic acid (EA) is a natural polyphenol that has been widely found in soft fruits, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“… 103 These studies suggest that the dopamine signaling pathway and the NLRP3 inflammasome are mutually regulated, and PD patients may benefit from inhibition of the inflammatory process in the neurons. 104 108 …”
Section: Roles Of Inflammasomes In Sterile Inflammatory Diseasesmentioning
confidence: 99%
“… 103 These studies suggest that the dopamine signaling pathway and the NLRP3 inflammasome are mutually regulated, and PD patients may benefit from inhibition of the inflammatory process in the neurons. 104 108 …”
Section: Roles Of Inflammasomes In Sterile Inflammatory Diseasesmentioning
confidence: 99%
“…These findings corroborate previous results from Wei et al (2020), who showed that treatment with ellagic acid (EA) resulted in improvements in the motor performance of rotenone-treated rats [ 40 ]. EA also has been reported to protect against 6-hydroxydopamine (6-OHDA) and lipopolysaccharide-induced DA neuronal damage and related motor impairment [ 41 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…EA, a component of PJ, has been reported to alleviate other non-motor symptoms, including hyperalgesia, cognitive deficiency, and memory performance in the 6-OHDA-induced rat model of PD [ 46 , 47 ]. Accumulating evidence supports the beneficial effect of treatment with EA, pomegranate’s natural precursor of UA, against DAergic neuronal loss and related DA depletion and motor and non-motor dysfunctions in PD models [ 41 , 42 , 43 , 44 ]. Recently, it has been demonstrated that treatment with extract of Eclipta alba rich in EA significantly downregulated the overexpression of α-synuclein at both protein and mRNA levels in the midbrain, prevented loss of DAergic neurons in SNpc, and mitigated behavioral deficits in the MPP+-mediated PD rat model [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result stands in contrast to observations made using a N9 murine microglial model, where a post in vitro digestion model of raspberries rich in ellagitannin and EA provided neuroprotection for up to 24 h post-LPS stimulation by suppressing the MAPK/NFAT/NF-ĸB signaling pathways [ 10 ]. In another study, EA pre-treatment decreased TNF-ĸ and NO production from BV-2 microglia by attenuating MyD88/NF-ĸB and p38/Erk/JNK signaling pathways after stimulation with a high dose of LPS (1 ug/mL) for 24 h [ 28 , 29 ]. The inconsistent potency of our whole red raspberry polyphenol extract with respect to regulating neuroinflammatory responses may stem from its composition, as it contains not only free EA but also significant amounts of anthocyanins and epicatechins.…”
Section: Discussionmentioning
confidence: 99%